Tarbawi Interpretation of the Educational Environment: Analysis of Qur’anic Verses on Family, School, and Community Education - M. Iqbal Gelar Budiman; B. Siti Mardliyah; Yulida Fauziyah; Ahmad Komarudin; Lukmanul Hakim; Hafidz Muslih (Jurnal test, 2026)
This study uses a tarbawi interpretation approach with a thematic (maudhu’i) method to analyse verses from the Qur’an concerning three educational environments: family, school, and society. The purpose of this study is to formulate a tri-centre education model based on Islamic principles. The analysis focuses on key verses: QS. At-Tahrim: 6 on the proactive and protective educational role of the family, QS. Al-Mujadalah: 11 on the nobility of scholars/scientists and ethics in scientific assemblies, and QS. An-Nahl: 125 on wise, advisory, and dialogical methods of preaching in community education. The results of the study indicate that each environment has a unique and complementary function. The family acts as the basic institution for instilling faith and morals through exemplary behaviour and habit formation. The school/academic environment serves as a place for intellectual development, instilling discipline and social values, and promoting knowledge. The community acts as an arena for the application of values, social interaction, and character building through wise lectures and positive social ethics. It is concluded that the success of holistic Islamic education requires an integrated and synergistic operational model, in which the three centres support each other continuously. The family provides a moral foundation, the school develops intellectual and social capacities, while the community provides a space for the practice and reinforcement of values, with the ultimate goal of realising khaira ummah. This research contributes to the development of applicable educational theory based on the perspective of the Qur’an.